Preparation of Polymethyl methalcrylate Rhodamine 6G and Its Optical Property - Kweon Jang, Won (Asian Journal of Chemistry, 2013)
Solid state Rhodamine 6G dye gain medium fabricated and discussed. Its optical properties are investigated for the all solid state tunable laser system in visible region. Among several methods of solidifying dye, the plastic method of using acrylic material of methymethalcrylate illustrated in detail that has never reported earlier. In optical inspection it showed a slightly distorted uniformity and bidirectional refractive indices. However, it has the good optical surface and there was not a serious scattering. Polymethyl methalcrylate Rhodamine 6G showed the nearly same absorption and fluorescence spectra compared to those of liquid state Rhodamine 6G.